Reaktualisasi Nilai-Nilai Profet Reactualizing Prophetic Qur’anic Values for Contemporary Social Challenges - Ulya, Miftah; Ari Masyhuri, Ahmad; Jawwas, Fahmi A; Nurhasanah, Nurhasanah; Mohammad, Wan Moharani bin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
Contemporary social challenges, such as moral crisis, social inequality, environmental degradation, and community disintegration, demand transcendent and universal value-based solutions. The purpose of this study is to re-actualize the Prophetic Values of the Qur'an for Contemporary Social Challenges. This research uses a qualitative approach based on library research, with the method of thematic analysis of Qur'anic verses containing prophetic values, such as justice (al-'adl), compassion (al-rahmah), honesty (al-sidq), and social responsibility (al-amanah). The analysis is carried out with a thematic interpretation perspective and supported by a social hermeneutics approach. This study found that prophetic values in the Qur'an have high relevance in responding to contemporary social issues, especially in shaping social ethics, strengthening community solidarity, and formulating spirituality-based public policy directions. These values are not only normative, but can also function as the basis for social transformation praxis. Reactualization of prophetic values in the Qur'an is constitutes an essential framework for promoting social justice, ethical conduct, and sustainability. Therefore, the development of a contextual and responsive interpretation approach to the Qur'an is essential.